PERLINDUNGAN HAK ASASI MANUSIA TERHADAP KEAMANAN PRODUK PANGAN DARI KEGIATAN BISNIS MULTINATIONAL CORPORATIONs (MNC) DI ERA GLOBALISASI - Sri Lestariningsih (Masalah-Masalah Hukum, 2011)
All the life process in society are changeover in the globalization era. The role of state is changed too by non state actors, namely Multinationals Corporations (MNCs). The MNCs have an authority to fulfill the food of society. Actually, the MNCs made his product without submissive the food safety products. The consequence of the dangerous food product from MNCs could threat the quality of right to life for society. Therefore, State should be active to control the bad effect in the process globalization with using the cosmopolitan law. Concerning to protection the human right getting the food safety from business activity by MNCs and reach the society welfare.